Reactorland A board game. - Makansi, J.
In this tongue-in-cheek game, players try to finance, license, and build a nuclear reactor in less time than the 5-10 years needed in real life
Keywords: Reactorland; Board game; Nuclear reactor construction; Nuclear reactor financing; Nuclear reactor licensing